Spatial distribution and determinants of missing essential newborn care items after birth in Somaliland: a spatial and multilevel analysis of SDHS - Dahir, Hana Mahdi; Korse, Ayan Husein; Mohamed, Farduus Ibraahim (Frontiers in Pediatrics, 2026)
BackgroundNeonatal mortality remains a critical global health issue, particularly in low- and middle-income countries, with suboptimal essential newborn care (ENC) practices contributing to poor outcomes. This study addresses the limited evidence on spatial variations and determinants of these gaps in contexts like Somaliland.MethodsThis study employed a community-based cross-sectional study design using data from the 2020 Somaliland Demographic and Health Survey (SDHS). A weighted sample of 2,314 mothers who gave birth in the five years preceding the survey was included. We performed spatial and multilevel analyses to identify determinants of missing essential newborn care. Multilevel logistic regression was used to identify individual and community-level factors, while Moran's I and Getis-Ord Gi statistics were applied to assess spatial autocorrelation and clustering.ResultsA high prevalence of missing essential newborn care (87%) was identified. Spatial analysis using Global Moran's I revealed significant positive spatial autocorrelation, indicating non-random clustering of missing care. Getis-Ord Gi statistics identified significant hot spots (areas with high missing care) in the eastern regions (Sanaag, Sool, and Togdheer) and cold spots (low missing care) in the western regions (Awdal and Marodijeh). Multilevel analysis revealed that delivery in a health facility dramatically increased the likelihood of receiving ENC (AOR = 6.17; 95% CI: 4.24–8.97) compared to home births. Mothers from middle (AOR = 2.16) and rich (AOR = 2.28) wealth quintiles were more likely to receive ENC, and children of average size were less likely to miss care (AOR = 0.46; 95% CI: 0.30–0.71).ConclusionThis study highlights a substantial unmet need for essential newborn care in Somaliland, driven by significant spatial disparities and strong associations with place of delivery and socioeconomic status. These findings call for targeted interventions promoting facility-based deliveries, addressing wealth-based inequalities, and strengthening regional health systems to enhance ENC coverage and improve neonatal survival.